Self-Selection in Physical and Mental Health among Older Intra-European Migrants - Amelie F. Constant; Nadja Milewski (Global Labor Organization (GLO), 2020)
The Healthy Immigrant Paradox found in the literature by comparing the health of immigrants to that of natives in the host country, may suffer from serious cultural biases. Our study evades such biases by utilizing a destination-origin framework, in which we compare the health of emigrants to that of their compatriots who stay in the country of origin. Isolating cultural effects can best gauge self-selection and host country effects on the health of emigrants with longer time abroad. We study both the physical and mental dimensions of health among European-born emigrants over 50, who originate from seven European countries and now live elsewhere in Europe. We use the Survey of Health, Ageing and Retirement in Europe and apply multi-level modeling. Regarding the physical health we find positive self-selection, beneficial adaptation effects, and effects from other observables for some but not all countries. With the notable exception of the German émigrés, we cannot confirm selection in mental health, while additional years abroad have only weak effects. Overall, living abroad has some favorable effects on the health of older emigrants. The economic similarity of countries and the free intra-European mobility mitigate the need for initial self-selection in health and facilitate the migration experience abroad.
Keywords: C23; F22; J11; J14; J15; J61; I12; I14; O52; 330; panel data; physical health; mental health; older population; emigrants; multi-level models; Europe